Desaprendizagem organizacional em empresas graduadas - Botelho, Érica de Aguiar (2016)
The aim of this study was to analyse how organizational unlearning occurs in ventures that have graduated from business incubation process. The research is exploratory, qualitative, with retrospective longitudinal time frame. A multiple case study was conducted, with the selection of six cases. Data was collected from semi-structured interviews, documentation and direct observations. Ventures and incubator perspectives were considered. Content analysis was taken. NVivo software was used to support the research. Based on theoretical backgrounds an analysis frame was elaborated in order to present the selected approaches. How organizational context of gradutated ventures that were bonded to a University Business Incubator in the technology sector can influence organizational unlearning was examined. Changes in organizational routines of graduated ventures were described, involving specific routines, from the new venture creation and development processes. Organizational unlearning was verified, predominantly in writing or updating business plan routine. Types of interplay between organizational learning and unlearning were identified. Isolated organizational learning was identified in every routine and all organizational unlearning situations were caracterized as isolated. Thus distinction between the two processes was corroborated. Situations where organizational unlearning precedes or occurs simultaneously to organizational learning were not observed. Relearning was verified only in writing or updating business plan routine. It was noticed that the context of these ventures offers opportunities for studying organizational unlearning not only after graduation but also during incubation period. Propositions were established based on venture incubation, new venture creation and development processes and organizational unlearning literatures.